Identifying putative cerebrospinal fluid biomarkers of amyotrophic lateral sclerosis in a north Indian population. Issue 4 (13th August 2020) - Khosla, Radhika; Rain, Manjari; Chawathey, Shreyas; Modgil, Shweta; Tyagi, Rahul; Thakur, Keshav; Pannu, Viraaj; Sharma, Suresh Kumar; Anand, Akshay
Abstract: Introduction: Evidence‐based information about cerebrospinal fluid (CSF) levels of biomarkers in patients with amyotrophic lateral sclerosis (ALS) is limited. Methods: Vascular endothelial growth factor (VEGF) and its receptor vascular endothelial growth factor receptor 2 (VEGFR2), optineurin (OPTN), monocyte chemoattractant protein‐1 (MCP‐1), angiogenin (ANG), and TAR DNA‐binding protein (TDP‐43) were quantified by enzyme‐linked immunoassay in the CSF of 54 patients with sporadic ALS and 32 controls in a case‐control study design. Results: CSF levels of VEGF ( P = .014) and ANG ( P = .009) were decreased, whereas VEGFR2 was higher ( P = .002) in patients with ALS than in controls. TDP‐43 positively correlated with MCP‐1 ( P = .003), VEGF ( P  < .001), and VEGFR2 ( P  < .001) in patients with ALS. Discussion: Our findings suggest possible utility of VEGF, VEGFR2, and ANG as biomarkers for use in ALS treatment trials.